Study on crack initiation and propagation in rock mass during unloading based on XFEM - DENG Qing-lin; ZHAO Guo-yan; TAN Biao; ZOU Yu-liang; LI Xi-bing (工程科学学报)
Rock-mass unloading often occurs during underground and slope engineering excavations. Here, rock-mass crack initiation and propagation during the excavation unloading progress was simulated using the extended finite element method (XFEM) in ABAQUS. Crack propagation and its influencing factors were studied and discussed after calculating the stress intensity factors at the crack tips, and by recording the crack's shape a dynamic evolution model was produced. The results show that the faster the unloading rate,the longer the crack,and the greater the crack dip angle, the easier the crack initiates. The normal stress on a crack surface decreases while shear stress increases during unloading, and that crack propagation is mainly controlled by shear stress. This is consistent with the theoretical analysis. The final shape of the modeled crack was also close to the result of the physical experiments, indicating the reliability of this study.